Pitarah Manusia Nusa Tenggara Timur Berdasarkan Ceritera Kromosom Y - Meti OFI Tefu; Ferry Fredy Karwur (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2017)
STUDY OF HUMAN ANCESTORS NUSA TENGGARA TIMUR INDONESIA BASED ON Y CHROMOSOME.Genetic studies conducted in NTT region focused on four islands namely Flores, Sumba, Alor, and Timor. The islands of NTT are a transition zone between Papuan and Austronesian speakers. Genetically there is also an intensive mixing. The dominant genetic of tribes in Alor island is Papua / Melanesia, but on the other islands there is almost uniform mixing. In the western part of Sumba Island there is a majority area of the Papuan/ Melanesian genetic type, while the tribes in eastern Sumba, Sabu and Rote are Austronesian. Genetic mixing is also seen on Timor Island. West Timor is the more dominantly Austronesian type, while central and eastern Timor are a mixture of Papua/ Melanesia with Austronesian. On such Flores islands, the tribes in the eastern and central regions have the Papua/ Melanesian type, while the western part is almost entirely of Austronesian type. The tribes on Solor, Lembata and Adonara Islands also have mixed types between Austronesia and Papua/ Melanesia. Based on paternal lineage, the blood flowing in NTT people consists of seven line ages of East Asia, Taiwan, Southeast Asia, Arab, Japan, Europe and Papua/ Melanesia, characterized by the detection of thirty-two Y-DNA markers: C-M130/ RPS4Y, F-P14/F-M89 (East Asia), NO-M214, O-M175, O-M119, O-M95, O-P203, O-M110, O-M122, O-M134, O-P201, O-JST3002611 (Taiwan), K-M526, K-P397, K-P405, K-P79, K-P336, P-P295, Q-M242, Q-P36 (Southeast Asia), J-M172 (Arab), C-P343, D-M116 (Japan), E-P1 (Europe),C-M38, C-M208, C-P355, M-P256, M-M4, M-P34, S-M230, S-M254, S-P377 (Melanesia).Studi genetik yang dilakukan di daerah NTT difokuskan pada empat pulau yakni Flores, Sumba, Alor, dan Timor. Pulau-pulau di NTT menjadi zona transisi antara penutur Papua dan Austronesia. Secara genetika juga terjadi pembauran yang intensif. Suku di pulau Alor, genetiknya dominan Papua/ Melanesia, namun di pulau-pulau lain terjadi pembauran hampir merata. Di Pulau Sumba bagian barat ada kawasan yang genetikanya mayoritas bertipe Papua/ Melanesia, sedangkan suku di Sumba bagian timur, Sabu dan Rote bertipe Austronesia. Pembauran genetika juga terlihat di Pulau Timor. Timor barat lebih dominan bertipe Austronesia sedangkan Timor bagian tengah dan timur merupakan campuran Papua/ Melanesia dengan Austronesia. Di pulau florespun demikian, yakni suku-suku di bagian timur dan tengah memiliki tipe Papua/ Melanesia, sedangkan bagian barat hampir seluruhnya memiliki tipe Austronesia. Suku-suku di pulau Solor, Lembata dan Adonara juga memiliki tipe campuran antara Austronesia dan Papua/ Melanesia. Berdasarkan garis keturunan ayah, darah yang mengalir dalam orang NTT terdiri atas tujuh garis keturunan yaitu Asia Timur, Taiwan, Asia Tenggara, Arab, Jepang, Eropa dan Papua/ Melanesia, yang ditandai dengan terdeteksinya tiga puluh tiga penanda Y-DNA yakni: C-M130/ RPS4Y, F-P14/F-M89 (Asia Timur), NO-M214, O-M175, O-M119, O-M95, O-P203, O-M110, O-M122, O-M134, O-P201, O-JST3002611 (Taiwan), K-M526, K-P397, K-P405, K-P79, K-P336, P-P295, Q-M242, Q-P36 (Asa Tenggara), J-M172 (Arab), C-P343, D-M116 (Jepang), E-P1 (Eropa),C-M38, C-M208, C-P355, M-P256, M-M4, M-P34, S-M230, S-M254, S-P377. (Melanesia)